Perceptions of causes of poor academic performance amongst selected secondary schools in Kericho Sub-County: Implications for school management. - Rono, Kenneth; Onderi, Henry; Owino, James (Kenya Journal Of Educational Planning, Economics & Management, 2014)
This Paper explores perceptions of causes of poor academic performance amongst selected secondary schools in Kericho sub-county and its implications for school management. It focuses on the relationship between family background and students’ poor academic performance in Kericho sub-county. Selected literature revealed that the major highlight on causes of poor academic performance is family background. However, there is need to find out what other factors are causing poor academic performances among students and the extent of these causes. It was discovered that the perception of parents, teachers and students was not any different as was reflected in the frequencies percentages and mean deviations. The study found out that majority of respondents agreed that perceptions are key to a students’ poor performance amongst other factors especially family background. Based on these results, this paper argues that there is need to sensitize stakeholders, give career guidance to students and have extra time for them. The paper suggests areas of further research on relationship between school factors and poor academic performance and impact of socio economic factors on academic performance on students. The paper is expected to give insight reference to policy makers, scholars and researchers in order to improve the weak areas. An effort is made to catch the attention of students, teachers and parents at the secondary school level who have attended the conference.
Keywords: Perception; Academic performance and school management